Analisis Kelayakan Bisnis Baitul Maal Wat Tamwil (Bmt) Maslahah Sidogiri Pasuruan: Pendekatan Multidimensional - akbar, yodi alrizky (Maliki Interdisciplinary Journal, 2025)
This business feasibility study uses a comprehensive multidimensional approach to analyze the potential and performance of Baitul Maal wat Tamwil (BMT) Maslahah Sidogiri in Pasuruan, East Java. The study was conducted through a comprehensive analysis covering law, environment, market, technology, HR management, and finance. This study was conducted using a qualitative-quantitative approach, and data was collected through documentation, interviews, and field observations. The results of the study indicate that BMT Maslahah has significant operational feasibility, with total assets reaching IDR 900 billion in 2023 and a customer base of more than 150,000 people. With a sharia financial market share of 6.8%, the company shows national asset growth of between 15 and 20 percent per year. However, there are recommendations for continuous improvement, especially in terms of information technology, HR development, and marketing strategy.